Sorting nexin 3 promotes ischemic retinopathy through RIP1- and RIP3-mediated myeloid cell necroptosis and mitochondrial fission - Jiaojiao Wang; Chunhong Zhou; Kai Zhuang; Jiami Zou; Wanlu Qiu; Mei Jin; Weile Ye; Pinglian Yang; Zhihua Zheng; Qing Zhou; Zunnan Huang; Yuanxiang Wang; et al. (Proceedings of the National Academy of Sciences, 2025)
Proliferative retinopathy is a leading cause of irreversible blindness in humans; however, the molecular mechanisms behind the immune cell–mediated retinal angiogenesis remain poorly elucidated. Here, using single-cell RNA sequencing in an oxygen-induced retinopathy (OIR) model, we identified an enrichment of sorting nexin (SNX)-related pathways, with SNX3, a member of the SNX family that is involved in endosomal sorting and trafficking, being significantly upregulated in the myeloid cell subpopulations of OIR retinas. Immunostaining showed that SNX3 expression is markedly increased in the retinal microglia/macrophages of mice with OIR, which is mainly located within and around the neovascular tufts. Myeloid cell-specific deficiency of Snx3 inhibited retinal neovascularization, hyperpermeability, and dysfunction in OIR mice. Using glutathione S-transferase pull-down, coimmunoprecipitation, and immunofluorescent staining, we found that SNX3 interacted with receptor-interacting protein 1/3 (RIP1 and RIP3). We further demonstrated that RIP1/3 degradation was accelerated in SNX3-deleted microglia/macrophages, causing an inhibition of hypoxia-induced necroptosis and mitochondrial fission, thereby decreasing the production of proinflammatory and proangiogenic factors (FGF2 and MMP12). Moreover, OIR retinas from myeloid cell–specific SNX3 overexpression transgenic mice presented more angiogenic tufts, while RIP1/3 inhibition largely ablated SNX3 overexpression–induced pathological angiogenesis. Based on the structure of SNX3, we identified a small-molecule inhibitor, W1122. Intriguingly, we found that W1122 effectively inhibited retinal angiogenesis in the OIR model, and combination treatment with anti-Vascular Endothelial Growth Factor (VEGF) yielded enhanced antiangiogenic effects. Collectively, our findings disclose a link between SNX3 and RIP1/3 signaling and implicate SNX3 in the development of ischemic retinopathy.